2021
DOI: 10.3390/pr9030410
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heavy Metals in the Sediments of Chalan Beel Wetland Area in Bangladesh

Abstract: This study aimed to determine the levels and possible sources of heavy metals (HMs) in the sediments of Chalan beel (a large lake-like aquatic ecosystem) area located in the northwestern part of Bangladesh. The mean concentrations (mg kg−1) of two HMs, Cd (6.22) and Pb (51.39) exceeded the world normal averages (WNA), whereas the mean concentrations (mg kg−1) of Ni (60.46), Zn (10.75), Mn (8.64) and Cu (4.71) were below the WNA. The sediments showed significant enrichment with Cd, Pb and Ni in the studied area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
(93 reference statements)
1
2
0
Order By: Relevance
“…No matter the season or region, the I geo of cadmium was higher, and the proportion of samples with heavy pollution degree was also higher than that of other metals. This is consistent with the pollution situation of Chalan Beel Wetland studied by Mohammad Abdus Salam et al [ 54 ]. R. Biddau et al [ 55 ] found that the uptake of Cd in asparagus was higher than that of other toxic elements, hence it is necessary to pay attention to the Cd content in the soil.…”
Section: Resultssupporting
confidence: 92%
“…No matter the season or region, the I geo of cadmium was higher, and the proportion of samples with heavy pollution degree was also higher than that of other metals. This is consistent with the pollution situation of Chalan Beel Wetland studied by Mohammad Abdus Salam et al [ 54 ]. R. Biddau et al [ 55 ] found that the uptake of Cd in asparagus was higher than that of other toxic elements, hence it is necessary to pay attention to the Cd content in the soil.…”
Section: Resultssupporting
confidence: 92%
“…In comparing the heavy metal and metalloid content with other research in a similar manner, it found that Fe and Cu concentrations were greater than the Buriganga river sediment as studied by Mohiuddin et al (2015) and , respectively. The Cr, Ni, and As concentration in the sediment in this study was much higher than the Buriganga river sediment studied by Akbor et al (2020) and the Mn, Cu, and Zn in the Chalan Beel wetland ecosystem studied by Salam et al (2021).…”
Section: Concentration and Distribution Of Heavy Metals And Metalloidscontrasting
confidence: 62%
“…Based on the current research, the authors suggest new measures for conserving fish diversity by minimizing the threats to these Belai beel wetlands. The reduction or minimization of the impacts of industrial activities [17,36], minimizing the uses of harmful insecticides and pesticides in agricultural crops, the proper application of fishing laws, education of fishermen communities [37] and raising public awareness can be effective for the conservation of existing fishery resources, and national strategies are being formulated for policymaking, monitoring and implementation in the Belai beel wetlands of Bangladesh [17,[38][39][40]. Determining the appropriate strategies with updated status information is also essential for conservation management and such data would help to focus the overall status of freshwater fish in the Belai beel, Bangladesh [40].…”
Section: Discussionmentioning
confidence: 99%